An unbeatable opponent?: Coaches’ perspectives on the impact of climate change in outdoor sports - Schneider, Sven; Reinmuth, Janina; Leer, Sophie (BMC sports science, medicine & rehabilitation, 2025)
Athletes in outdoor sports particularly experience several consequences of climate change. To take up the experiences and expectations of coaches in outdoor sports regarding climate-related health risks in sport and to systematize them. This nationwide, cross-sectional study was conducted among adult outdoor sports coaches from the ten largest outdoor sports associations in Germany. Their experiences with climate-related changes where were collected and qualitative content analysis was conducted. Out of 1,771 participating coaches, the content-analytical evaluation resulted in eight disjointed topics. These comprise heat-related risks, accident and injury risks, UV-related risks, respiratory risks, infection risks, mental risks and also positive effects of climate change. Besides, statements of respondents not expecting any significant changes due to climate change were recorded. In the course of climate change, sport-specific risks will continue to increase and especially the risk setting of outdoor sports will be confronted to them. In order to be able to practice sports successfully and safely in the future, the study results emphasize the necessity to develop comprehensive, flexible and cost-effective prevention concepts for climate adaptation in sports. Clinical trial number: The study protocol was pre-registered with the German Clinical Trials Registry (registration number DRKS00027815) on January 18, 2022 ( https://drks.de/search/de/trial/DRKS00027815 ).